Home Automation based on Raspberry Pi - tri raharjo yudantoro (Politeknik Negeri Semarang, 2016)
Every human being wants to feel safe and comfortable when traveling or leaving home empty. in addition to feeling safe and comfortable, homeowners also want electronic equipment at home can be controlled easily to reduce the waste of electricity and can know the condition of the house remotely.therefore, a home automation system is needed which enables homeowners to travel to control the use of electronic devices at home and to know the state of the house, accessible wherever and whenever. With the existence of these problems then made the final task with the title Home Automation based Raspberry PI.the purpose of this final task is to make Home Automation system with Raspberry PI, LDR sensor, RTC and PIR sensors. This system is used to control lights and webcam automatically. The LDR sensor is used to get the light intensity to automate the lamp.rTC is used to get the current time on Raspberry Pi which then can be used to turn the lights on and off. The PIR sensor is used to read the human movement which then for the automation of the webcam in taking pictures of the state of the house. This system can also be controlled manually on a smartphone by using Telegram Bot inside Telegram app.the methodology used in designing this system is waterfall. The system is tested by creating a home model containing lights inside the house and outdoors.the results of testing with questionnaires conducted to 10 respondents obtained level of satisfaction of 79.2% which means Raspberry Pi Home-based system satisfactory.